Navigating Exploitative and Explorative Leadership in Support of Infrastructure Resilience - Helmrich, Alysha; Chester, Mikhail (Frontiers in Sustainable Cities, 2022)
Leadership is a critical component in approaching infrastructure resilience. Leadership, the formal and informal governance within an organization, drives an infrastructure system's ability to respond to changing circumstances. Due to the instability of the Anthropocene, infrastructure managers (individuals who design, build, maintain, and decommission infrastructure) can no longer rely on assumptions of stationarity, but instead that shifts are occurring at a faster rate than institutions and infrastructure organizations are adapting. Leadership and organizational change literature provide considerable insights into the ability of organizations to navigate uncertainty and complexity, and infrastructure organizations may be able to learn from this knowledge to avoid obsolescence. Therefore, this article asks: what leadership capabilities do infrastructure organizations need to readily respond to stability and instability? An integrative leadership framework is proposed, exploring capabilities of collaboration, perception and exploration toward learning, and flexible informal and formal governance leveraged by leadership. These capabilities are driven by underlying tensions (e.g., climate change, emerging technologies) and managed through enabling leadership, a set of processes for pivoting between stability and instability. The framework is then applied to infrastructure organizations. Lack of market competition may make infrastructure organizations more open to collaboration and, therefore, learning. However, the need to provide specific services may cause risk adversity and an avoidance of failure, restricting flexibility and innovation. It is critical for infrastructure organizations to identify their strengths and weaknesses so they may develop an approach to change at pace with their external environments.